2011
DOI: 10.1002/for.1258
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the Yield Curve in a Data‐Rich Environment Using the Factor‐Augmented Nelson–Siegel Model

Abstract: Various ways of extracting macroeconomic information from a data-rich environment are compared with the objective of forecasting yield curves using the Nelson-Siegel model. Five issues in factor extraction are addressed, namely, selection of a subset of the available information, incorporation of the forecast objective in constructing factors, specification of a multivariate forecast objective, data grouping before constructing factors, and selection of the number of factors in a data-driven way. Our empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…The methodology of relating observed variables to a small set of factors has been employed in the forecasting of inflation and production data, see Massimiliano et al (2003), asset returns and volatilities, see e.g. Ludvigson and Ng (2007), and the term structure of interest rates, see Exterkate et al (2010). These studies have reported favorable results when such macro factors are used for forecasting.…”
Section: The Econometric Frameworkmentioning
confidence: 97%
“…The methodology of relating observed variables to a small set of factors has been employed in the forecasting of inflation and production data, see Massimiliano et al (2003), asset returns and volatilities, see e.g. Ludvigson and Ng (2007), and the term structure of interest rates, see Exterkate et al (2010). These studies have reported favorable results when such macro factors are used for forecasting.…”
Section: The Econometric Frameworkmentioning
confidence: 97%
“…() and Exterkate et al . () document that macro factors contain valuable predictive information. Third, several recent papers use survey data in analysis of the term structure.…”
Section: Introductionmentioning
confidence: 99%
“…This provides us with a panel of 480 monthly observations on 17 different maturities. Similar but shorter datasets have been considered by Moench (), Exterkate et al () and Laurini and Hotta ().…”
Section: Data and Comparison Of Forecasting Modelsmentioning
confidence: 76%
“…This approach is the so‐called equilibrium or affine‐class models, where time series techniques are used to model the dynamics of yield on a short‐term or instantaneous maturity, and yields for longer maturities are then derived using an affine model. In the context of yield curve forecasting with Nelson–Siegel type models, de Pooter et al (), Moench (), Exterkate et al () and Koopman and van der Wel () document that macro factors contain valuable predictive information.…”
Section: Introductionmentioning
confidence: 99%